IMPORTANCE OF VIRECHANA IN VATARAKTA - Dr Saeeda M Makandar; Dr G S Badrinath; Dr Pavithra Viraktmath (EPRA International Journal of Research and Development (IJRD), 2023)
Vatarakta is a vitiation of vata dosha and rakta dhatu and normal flow of vata obstructed by vitiated rakta dhatu it can be merely compare with metabolic disorder gout which is a common type of arthritis due to uric acid disturbance. In ayurveda there are different causative factors, types, pathogenesis and treatment modalities are explained. Virechana karma has a less complication and is effective in vitiated pitta dosha, rakta dhatu. So here in detail about the disease is explained along with specific line of treatment, and different yogas for the virechana karma in different conditions has been explained.